Skill biased labour demand and the wage growth of younger workers: Evidence from an unexpected pension reform - Alexander Danzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Large-scale pension reforms can have redistributive wage effects across generations and education groups when the labour market suffers from skill mismatch. A quasi-experimental retirement shock in Ukraine illustrates the effect of labour scarcity on wage growth and returns to education: it reveals that young and well educated workers enjoyed significant wage growth accelerations while older workers with outdated skills did not benefit from the retirement of their comparable peers. The estimated wage effects are in line with predictions from a simple heterogeneous labour demand model applied to a cross-section of Ukrainian firms. The paper illustrates that general equilibrium wage effects can be estimated in a policy evaluation framework if quasi-experiments fulfil very restrictive preconditions.
Keywords: J20; J31; P23; 330